The Use of Virtual Reality in the Teaching of Challenging Concepts in Virology, Cell Culture and Molecular Biology - Reen, F. Jerry; Jump, Owen; McSharry, Brian P.; Morgan, John; Murphy, David; O’Leary, Niall; O’Mahony, Billy; Scallan, Martina; Supple, Briony (Frontiers in Virtual Reality, 2021)
The rapidly expanding biotechnology sector horizon is expected to create a surge in demand for expertise underpinning cell and gene therapies, which are recognized as the next generation of medicines. New and innovative approaches to implement active and performative learning in the Molecular Life Sciences are required to support this and to address limitations associated with traditional ‘front of class’ lectern delivery of challenging, three dimensional molecular concepts. Therefore, an immediate need exists for the development and implementation of immersive learning approaches in Virology, Cellular Sciences and Molecular Biology to underpin sustainable development of graduate students for academic and industrial research careers. The Covid-19 pandemic has led to significant changes in the delivery of education globally, with online engagement and accelerated uptake of novel teaching and assessment modalities into majority practice within institutions. This development has been driven by externally imposed necessity and it remains to be seen what form teaching and learning will take post-Covid. Irrespective of the pandemic, technologies are available which can serve intrinsically motivated, discipline specific shifts toward enhanced learner experiences and learning outcomes. Immersive virtual reality offers one such approach to open new entry points for student learning of abstract molecular concepts, which will be just as relevant upon our return to face-to-face teaching. Key to delivering this will be engagement and collaboration by disciplinary and technical experts. Here, we discuss global advances in the area of VR and Molecular Science education and assess potential paths forward for teaching and learning impact and innovative education.